Block-based optimization for enhancing reversible watermarking using reduce difference expansion - Arham, Aulia; Adi Nugroho, Hanung (Communications in Science and Technology, 2024)
In recent years, reversible watermarking has emerged as a promising technique that safely embeds data in digital images without compromising their originality. This method is particularly useful for sensitive images such as military, art, and medical images, where each pixel contains important information requiring authentication. Researchers have been attempting to develop this method further to increase payload capacity while maintaining visual quality and low computational complexity. In this study, we developed a reversible watermarking with block-based optimization based on Reduced Difference Expansion (RDE) applied to 3×3 pixel blocks, allowing for the embedding of 8?bit data. Based on experimental results from tests conducted on 2 common images and 3 medical images, our method could consistently achieve a payload capacity of up to 0.8924 bpp with a PSNR of 41.077 dB while maintaining good visual quality across various image categories, outperforming previous approaches.